The origins of national financial systems : Alexander Gerschenkron reconsidered - Forsyth, Douglas J. (Douglas James), 1955-; Verdier, Daniel, 1954- (London ; New York : Routledge, 2003)
This book poses a systematic challenge to Gerschenkron's 1950s thesis on universal banks. With contributions from leading scholars including Ranald Michie and Jaime Reis, it provides solid and intriguing arguments throughout.
The origins of universal banks in France during the nineteenth centuryBanking systems as ~ideal types~ and as political economy: the Swedish case, 1820 1914; The development of a hybrid structure in Norway: banks and economic change in the European periphery, 1870 1913; Universal banking in Russia; Bank structures, Gerschenkron and Portugal (pre-1914); Works cited; Index.
Includes bibliographical references (pages 205-229) and index.
Master record variable field(s) change: 050, 082
Keywords: Gerschenkron, Alexander; Gerschenkron, Alexander; Banks and banking -- History; Investment banking -- History; Universal banks -- History; BUSINESS & ECONOMICS -- Banks & Banking; Banks and banking; Investment banking; Universal banks; Bankwezen; Electronic books; History